Provenancing antiquarian museum collections using multi-isotope analysis - Neil, S; Evans, J; Montgomery, J; Schulting, R; Scarre, C (The Royal Society, 2023)
Many of the most significant archaeological sites in Europe were excavated by antiquarians over one hundred years ago. Modern museum collections therefore frequently contain human remains that were recovered during the nineteenth and early twentieth centuries. Here we apply multi-isotope analysis (87Sr/86Sr, δ18O, δ13C, δ15N) and 14C dating to evaluate the provenance of human remains within a collection that is thought to have been recovered from one of the most important archaeological sites in Britain. Excavated in 1910, the site of Coldrum in Kent is a megalithic burial monument that may be one of the earliest sites associated with the transition to farming in Britain. The interpretation of this site is therefore key to understanding how agriculture began. Using isotope analysis we show that although the human skeletal collections attributed to Coldrum do contain some of the earliest dated Neolithic human remains in Britain, they also contain the remains of individuals of fifth to seventh centuries AD date. We evaluate subsistence and mobility patterns of early Neolithic populations and provide new information about the origins of those individuals in the collection that date to the fifth to seventh centuries AD. We demonstrate the utility of employing isotope analysis to provide direct and independent information about the provenance of human remains in museum collections.